Investigations into the Logistics of Ignatius’s Itinerary - Altena, Vincent van (Journal of European Baptist Studies, 2021)
From the post-apostolic era several writings have been handed down to us which provide a glimpse into the developments of Christianity in the early second century CE. Among these writings are seven letters of Ignatius, the bishop of Antioch who was led in captivity into Rome to die a martyr’s death. During his travels Ignatius wrote a number of letters to Christian churches. The aims of this article are (1) to offer possible geographical reconstructions of Ignatius’s travels to Rome and (2) to analyse the social world that can be extracted from Ignatius’s letters and other contemporary sources (e.g. Polycarp’s letter to the Philippians). This may enable us to visualise the relationships between Ignatius and the congregations as well as to gain insights into the social coherence of early Christianity.